TET Methylcytosine Oxidases in T Cell and B Cell Development and Function - Tsagaratou, Ageliki; Lio, Chan-Wang J.; Yue, Xiaojing; Rao, Anjana (Frontiers in Immunology, 2017)
DNA methylation is established by DNA methyltransferases (DNMTs) and is a key epigenetic mark. Ten Eleven Translocation (TET) proteins are enzymes that oxidize 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC) and further oxidization products (oxi-mCs), which indirectly promote DNA demethylation. Here, we provide an overview of the effect of TET proteins and altered DNA modification status in T and B cell development and function. We summarize current advances in our understanding of the role of TET proteins and 5hmC in T and B cells in both physiological and pathological contexts. We describe how TET proteins and 5hmC regulate DNA modification, chromatin accessibility, gene expression and transcriptional networks, and discuss potential underlying mechanisms and open questions in the field.